25 Years since CTBT: A Possible bridge between Nuclear Powers? - Herrera, M.; Shivani, S. (Spanish Institute of Strategic Studies, 2021)
The Comprehensive Nuclear-Test-Ban Treaty (CTBT) was drafted 25 years ago. Since then, like the 1968 Nuclear Non-Proliferation Treaty (NPT), it has received quasi-majority support from the entire international community. However, unlike the NPT, the CTBT has not yet entered into force due to the lack of ratification by the States listed in Annex II of the treaty. This article aims to explore the main reasons why four of the eight non-ratifying states (the U.S., China, India and Pakistan) have not yet ratified the treaty, as well as suggest possible areas of convergences between emerging nuclear weapon powers like India, China and Pakistan and the nuclear superpower that is, the U.S. that can eventually bring about the treaty’s entry into force